Need analysis of English skill for business materials - Rama Dwi Putrilani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2018)
Need analysis is process collecting the information from stakeholder (Educational Institution and Company) about the learners’ need. Need analysis is needed before the materials are used. It is done to identify the materials needs the students based on stakeholder’s perspectives. It gives us a suitable material for the learners’need and the target need. The aim of this research was to find the English skill most needed for Business materials of Business Administration student at Politeknik Negeri Padang. The type of this research was a survey research. The data were collected through questionnaire and interview. The sources of questionnaire data were 20 students of Business Administration at Politeknik Negeri Padang, 3 lecturers of Business Administration at Politeknik Negeri Padang, 20 staff of Telkom West Sumatera, and 36 staff of Bank Nagari. The sources of interview data were 2 students of Business Administration at Politeknik Negeri Padang, 3 English lecturers of Business Administration at Politeknik Negeri Padang, 1 chief of Business Administration at Politeknik Negeri Padang, 2 staffs of company at Telkom Sumbar, 6 staffs of company at Bank Nagari. The finding of this research shows that the material needed by learners more emphasized on English skill of students ; speaking, listening, and reading.